Amelioration of Brain Damage after Treatment with the Methanolic Extract of Glycyrrhizae Radix et Rhizoma in Mice - Myeongjin Choi; Chiyeon Lim; Boo-Kyun Lee; Suin Cho (MDPI AG, 2022)
Glycyrrhizae Radix et Rhizoma (GR) is a traditional herbal medicine widely used in Asian countries. GR was the most frequently used medicine among stroke patients in Donguibogam, the most representative book in Korean medicine. In the present study, we investigated the neuroprotective effects of the GR methanolic extract (GRex) on an ischemic stroke mice model. Ischemic stroke was induced by a 90 min transient middle cerebral artery occlusion (MCAO), and GRex was administered to mice with oral gavage after reperfusion of MCA blood flow. The MCAO-induced edema and infarction volume was measured, and behavioral changes were evaluated by a novel object recognition test (NORT). Immunofluorescence stains and Western blotting identified underlying mechanisms of the protective effects of GRex. GRex post-treatment in mice with MCAO showed potent effects in reducing cerebral edema and infarction at 125 mg/kg but no effects when the dosage was much lower or higher than 125 mg/kg. GRex inhibited the decrease of spontaneous motor activity and novel object recognition functions. The neuroprotective effects of GRex on ischemic stroke were due to its regulation of inflammation-related neuronal cells, such as microglia and astrocytes.